Analisis Faktor-Faktor Yang Mempengaruhi Konsep Diri dan Moralitas Remaja dari Aspek Sosial-Religius - Lbs, Freddy Hermansyah; Ichsan, Ichsan (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2023)
Self-concept and morality are the most important things that must be considered in the development of a teenager because of their enormous influence. The purpose of this study was to determine the factors that influence adolescent self-concept and morality. The research method used in this study is qualitative research in which the data is obtained by conducting library research using a penomelogy approach. The results of this study are the factors that influence adolescent self-concept are physical factors, family factors, and other people's reactions to individuals while the factors that affect adolescent morality are parental attention, adolescent psychological pressure, and advances in modern technology.